2011
DOI: 10.1016/j.jclepro.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Costs and carbon emissions for geopolymer pastes in comparison to ordinary portland cement

Abstract: a b s t r a c tGeopolymer concrete is seen as a potential alternative to standard concrete, and an opportunity to convert a variety of waste streams into useful by-products. One key driver in geopolymer development is the desire to reduce greenhouse gas emissions from the production of concrete products. This paper presents an examination of the lifecycle cost and carbon impacts of Ordinary Portland Cement (OPC) and geopolymers in an Australian context, with an identification of some key challenges for geopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
506
1
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,451 publications
(530 citation statements)
references
References 18 publications
7
506
1
16
Order By: Relevance
“…Significant material resources exist in the UK for producing geopolymer concrete, including large stockpiles of PFA [67]. This could yield reductions in embodied emissions of 36-56% compared with OPC 5 [68]. However, it will likely be decades before production reaches a substantial scale [66].…”
Section: Substitution In the Production Of Common Materialsmentioning
confidence: 99%
“…Significant material resources exist in the UK for producing geopolymer concrete, including large stockpiles of PFA [67]. This could yield reductions in embodied emissions of 36-56% compared with OPC 5 [68]. However, it will likely be decades before production reaches a substantial scale [66].…”
Section: Substitution In the Production Of Common Materialsmentioning
confidence: 99%
“…Although it has been demonstrated that AAC production involves significant reduction in CO2 emissions [34], industry confidence in AAC needs to be built gradually from both a technical and commercial standpoint. There are only a few examples of AAC in long term structural applications (more than 50 years use) that can demonstrate the long service life of this emerging construction material [4].…”
Section: Pathways To Commercialisation and The Role Of Researchmentioning
confidence: 99%
“…Many of the precursors which are used to produce alkali-activated binders are also in demand for use in blends with Portland cement, and this competition for raw materials must also be taken into consideration in any discussion of the supply chains related to alkali-activated materials. If alkali-activated materials are to be promoted as an environmentally beneficial option, the transport of bulk materials must obviously be minimized, as this can dominate the emissions footprint of the binder as a whole if materials must be transported long distances [9]. This therefore brings a focus on the development and utilization of locally available materials as precursors to alkali-activated binders.…”
Section: Introductionmentioning
confidence: 99%